Analysis of the Distribution of Forest Management Areas by the Forest Environmental Tax in Ishikawa Prefecture, Japan - Yuta Uchiyama; Ryo Kohsaka (International Journal of Forestry Research)
Forest management approaches vary according to the needs of individual municipalities with unique geographic conditions and local social contexts. Accordingly, there are two types of subsidies: a unified national subsidy and a prefecture-level subsidy, mainly from forest environmental taxes. The latter is a local tax. Our focus is on examining forest management using these two types of taxes (i.e., central and prefecture-level) and their correlations with social and natural environmental factors. In this paper, we examine the spatial distribution of management areas using subsidies from the central government, the Forestry Agency of Japan, and prefectural forest environmental taxes in Ishikawa. In concrete terms, the spatial correlations of the management areas under two tax schemes are compared with the natural hazard areas (as a natural environmental factor) and areas with high aging rates (as a social factor). The results are tested to see whether the correlations of areas with the two factors are significant, to examine whether the taxes are used for areas with natural and social needs. From the result, positive correlations are identified between the distribution of management areas and natural hazard areas and between the distribution of management areas and areas with high aging rates.